2006
DOI: 10.1183/09031936.06.00002506
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis outbreak among students in a boarding school

Abstract: Tuberculosis (TB) outbreaks present a public health challenge. Six cases of active TB emerged in a boarding school in Israel during 1 yr. An epidemiological outbreak investigation was performed, followed by implementation of control measures.The investigation included interviews, tuberculin skin test (TST) and chest radiographs of the students. Close contact (n5155) was defined as being in the same class or dormitory with a patient. Remote contact (n5246) was defined as being in the school.An epidemiological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 20 publications
1
21
0
1
Order By: Relevance
“…They experience high stress, lack adequate sleep or effective exercise, have poor physical fitness and decreased immunity, which make them susceptible to TB infection. Meanwhile the students’ classrooms, dormitories and other environments are highly crowded, which also provide conditions for the outbreak of the epidemic [17, 18]. High school students are in a critical period of physical and psychological growth, which is a high-risk period for psychological conflict and behavioral, emotional problems as well [19].…”
Section: Introductionmentioning
confidence: 99%
“…They experience high stress, lack adequate sleep or effective exercise, have poor physical fitness and decreased immunity, which make them susceptible to TB infection. Meanwhile the students’ classrooms, dormitories and other environments are highly crowded, which also provide conditions for the outbreak of the epidemic [17, 18]. High school students are in a critical period of physical and psychological growth, which is a high-risk period for psychological conflict and behavioral, emotional problems as well [19].…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies also revealed high risk of acquiring TB infection and subsequent transmission among college students [7–18]. A study conducted among students of Jimma University, southwest Ethiopia, showed that contact in the campus to students who have TB seems to be one of the major factors responsible for the acquisition of TB [19].…”
Section: Introductionmentioning
confidence: 99%
“…TB in certain populations, including in educational institutions, has been reported among students in low-endemic countries, such as England, Italy, Ireland, and several states in the USA [15]. Similar research conducted in China in 2015 reported a case of TB outbreak in a middle school with 46 active TB cases (17.8%) among 258 students and 15 teachers [11].…”
Section: Introductionmentioning
confidence: 73%
“…The research, based on current data, found that smoking habits are responsible for 23% of TB suspect cases, while environmental factors are responsible for 26% of all cases [10]. Moreover, the rate of infection risk caused by environmental factors has shown that there is an epidemiological association amounting to 99.2%, being significantly affected by close contact [15,16].…”
Section: Introductionmentioning
confidence: 99%